Dampak Jarak Tanam Terhadap Kompeti Nutrisi dan Cahaya pada Tanaman Bayam (Amaranthus SPP.) - Destri Natalis Harefa; Selvin Septiani Warwu; Dodi Roni Yanto Waruwu; Ayler Beniah Ndraha (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
Spinach (Amaranthus spp.) is a vegetable plant that is highly dependent on the availability of light and nutrients for its growth. Proper spacing plays an important role in influencing a plant's access to light and nutrients, which ultimately impacts its yield. This study examines the impact of planting distance on light and nutrient competition in spinach. Planting spacing that is too tight can lead to intense competition between plants, reduce the efficiency of photosynthesis, and increase the risk of etiolation in lower plants. On the contrary, planting spacing that is too wide reduces land use efficiency and increases the likelihood of weed growth. The ideal planting distance ranges from 15-20 cm between plants, which ensures maximum utilization of light and nutrients without resulting in excessive competition, thus supporting optimal growth and yield